PENGARUH FINANCIAL KNOWLEDGE, FINANCIAL BEHAVIOR DAN FINANCIAL ATTITUDE TERHADAP PERSONAL FINANCIAL MANAGEMENT - Herma Wiharno (Program Studi Akuntansi, Universitas Kuningan, 2018)
This study aims to examine the influence of financial knowledge, financial behavior and financial attitude toward personal financial management. Tests in this study using multiple linear regression analysis. The research method used in this research is verifikatif method. The object of this research is the community in Kuningan Regency with the analysis unit is civil servant. The sampling technique of this research using Cluster Proportional Random Sampling method. The results showed that the variable of financial knowledge, financial behavior, and financial attitude partially have a significant positive effect on personal financial management, meaning that partial improvement of financial knowledge, financial behavior and financial attitude variable will cause an increase in the variable of personal financial managementKeywords: financial knowledge, financial behavior, financial attitude dan personal financial management